Differential Role of Smad2 and Smad3 in the Acquisition of an Endovascular Trophoblast-Like Phenotype and Preeclampsia - Brkić, Jelena; Dunk, Caroline; Shan, Yanan; O'Brien, Jacob Anderson; Lye, Phetcharawan; Qayyum, Sheza; Yang, Peifeng; Matthews, Stephen G.; Lye, Stephen J.; Peng, Chun (Frontiers in Endocrinology, 2020)
During placental development, cytotrophoblast progenitor cells differentiate into the syncytiotrophoblast and invasive extravillous trophoblasts (EVTs). Some EVTs further differentiate into endovascular trophoblasts (enEVTs) which exhibit endothelial-like properties. Abnormal placental development, including insufficient enEVT-mediated remodeling of the uterine spiral arteries, is thought to be a precipitating factor in the onset of preeclampsia (PE), a pregnancy-related hypertensive disorder. Several members of the transforming growth factor-β (TGF-β) superfamily, such as TGF-βs, Nodal, and Activin have been reported to either promote or inhibit the invasive EVT pathway. These ligands signal through serine/threonine receptor complexes to activate downstream signaling mediators, Smad2 and Smad3. In this study, we determined Smad2 and Smad3 expression pattern in placenta and their effects on trophoblast invasion and differentiation. Total Smad2/3 levels were relatively constant across gestation while the ratio of active phosphorylated forms to their total levels varied with gestational stages, with a higher pSmad2/total Smad2 in later gestation and a higher pSmad3/total Smad3 in early gestation. Immunofluorescent staining revealed that pSmad3 was localized in nuclei of EVTs in anchoring villi.  On the other hand, pSmad2 was mostly absent in this invasive EVT population. In addition, pSmad3/total Smad3, but not pSmad2/total Smad2, was significantly lower in both early onset and late onset PE cases, as compared to gestational age-matched controls. Functional studies carried out using a first trimester trophoblast cell line, HTR-8/SVneo, and first trimester human placental explants showed that Smad2 and Smad3 had differential roles in the invasive pathway. Specifically, siRNA-mediated knockdown of Smad2 resulted in an increase in trophoblast invasion and an upregulation of mRNA levels of enEVT markers while the opposite was observed with Smad3 knockdown. In addition, Smad2 siRNA accelerated the EVT outgrowth in first trimester placental explants while the Smad3 siRNA reduced the outgrowth of EVTs when compared to the control. Furthermore, knockdown of Smad2 enhanced, whereas overexpression of Smad2 suppressed, the ability of trophoblasts to form endothelial-like networks.  Conversely, Smad3 had opposite effects as Smad2 on network formation. These findings suggest that Smad2 and Smad3 have opposite functions in the acquisition of an enEVT-like phenotype and defects in Smad3 activation are associated with PE.